First cockroaches (Insecta: Blattaria: Blattulidae) from the Lower Cretaceous Sinuiju Formation, Democratic People's Republic of Korea: Associated fossil plant assemblages and paleoclimatic inferences. (October 2021) - So, Kwang-Sik; Won, Chol-Guk
Abstract: Several cockroach specimens were recovered from the Sinuiju Formation in Paektho-dong, Sinuiju City, North Phyongan Province, Democratic People's Republic of Korea (DPRK). These specimens belong to Habroblattula drepanoides Wang, Liang et Ren, 2007. Fossil plant assemblages also recovered from the Sinuiju Formation are typical of Early Cretaceous floras from warm to temperature regions. Highlights: Habroblattula drepanoides is firstly described from the Sinuiju Formation. The remarkable taxa belong to the family Blattulidae. These materials reveal fine details of the family Blattulidae. These new taxa also fill a blank in Blattulidae study in Sinuiju region. The Sinuiju flora is one of the Early Cretaceous floras in the warm-temperate zone.